2014
DOI: 10.1002/pc.23198
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion and dynamic property in SBR/silica composites: Revisiting the utilization of benzyl chloride silane

Abstract: Separating the effects of interfacial interaction on rubber performance from those of the dispersion state remains challenging, as an improvement in both properties is often observed upon addition of an interfacial modifier. In this work, 4-(chloromethyl) phenyltrimethoxysilane, a silane-bearing benzyl chloride, is used as the model substance to modify a SBR/silica composite. Although an improvement in dispersion, as indicated by morphological observations and rheological measurements, is achieved, the dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…Several studies have been conducted on LAOS behavior of uncured filled rubber compounds. The Payne effect, mentioned earlier, is also observed in unvulcanized filled rubber compounds, including SBR/silica compounds 99–115 . It has been shown that the Payne effect increases with silica loading, surface area, and aspect ratio.…”
Section: Introductionmentioning
confidence: 61%
“…Several studies have been conducted on LAOS behavior of uncured filled rubber compounds. The Payne effect, mentioned earlier, is also observed in unvulcanized filled rubber compounds, including SBR/silica compounds 99–115 . It has been shown that the Payne effect increases with silica loading, surface area, and aspect ratio.…”
Section: Introductionmentioning
confidence: 61%
“…The SEM micrograph of SBR/SiO 2 vulcanizates as shown in Fig. 2a indicates that silica is unevenly dispersed in the SBR matrix as large agglomerates because of the formation of hydrogen bonds among the abundant silanol groups on its surface [34]. On the contrary, the SBR/GO vulcanizates as presented in Fig.…”
Section: Sem Failure Surface and Fracture Surface Morphologymentioning
confidence: 99%
“…然而, 将含有苄基氯的硅烷偶联剂应用于 丁苯橡胶, 得到的橡胶复合材料在动态性能方面却 没有提高. Feng等人 [51] 图 4 (网络版彩色)白炭黑修饰机理示意图 [52] Figure 4 (Color online) Schematic diagram of the modification mechanism of silica [52] 相比于TESPT, 单官能团的偶联剂如双(二甲基 [53] .…”
unclassified